Performance Analysis of Fiber Optic Current Sensor using Sagnac Interferometer - Idris@Othman, S. K.; Haroon, H.; Abdul Razak, H.; Mohd Zain, A. S.; Jaafar, H. (Journal of Engineering and Technology (JET), 2022)
In conventional current sensors the accuracy, sensitivity, reliability, and safety are greatly affected by electromagnetic interference phenomena. The advancement of fiber optic technology in recent years opened up a better solution to this problem. The motivation of this project is to implement and enhance fiber optic as a current sensor. A fiber optic interferometer is applied to receive inputs from a modulator, which resemble the presence of an electromagnetic field around a conductor carrying an electrical current. This research is to design and demonstrate a fiber optic current sensor using Sagnac interferometric scheme. The design is simulated using Optisystem software. The performance of the fiber optic current sensor was observed and analyzed. Analysis has focused on the output waveform, transmission losses, power consumption, and sensitivity of the device based on the Pulse mode and CW mode. CW mode laser had a more stable and steady waveform however the power consumption and transmission losses are higher compared to pulse mode. For pulse mode, at a higher frequency, the sensitivity of the proposed fiber optic current sensor design is decreased.